THE APPLICATION OF CORPUS TECHNOLOGY TO IMPROVE STUDENTS' READING SKILL - Karnaeni, Karnaeni; Dj, Muhammad Zuhri; Musfirah, Musfirah (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This research aims to determine the application of corpus technology to improve students' reading skills at SMAN 26 Bone. The participants in this research were students of class XI IPS 2 SMAN 26 Bone with a sample of 20 students selected using cluster random sampling technique. In this research, the researcher used quantitative method with pre-experimental design. In addition, the instrument used was a test where the test consisted of pre-test and post-test. In the data analysis technique, the researcher used the SPSS version 23 program. The results of this research showed that the average value of class students in the pre-test (34.75) and post-test (65.00) after being given Corpus Technology treatment. The t-test value showed that the sig. (2-tailed) of 0.00 which means 0.00 <0.05. Based on the description above, the Alternative Hypothesis (Ha) of this research is accepted and the Null Hypothesis (H0) of this research is rejected. Based on this, it can be concluded that Corpus Technology is effectively used to improving students' reading skills at SMAN 26 Bone.Â